Monitoring of Outpatient Parenteral Antimicrobial Therapy and Implementation of Clinical Pharmacy Services at a Community Hospital Infusion Unit. (October 2015) - Shah, Punit J.; Bergman, Scott J.; Graham, Donald R.; Glenn, Stephanie
Background: In 2004, the Infectious Diseases Society of America (IDSA) published monitoring guidelines for outpatient parenteral antimicrobial therapy (OPAT), but no assessment of their utilization has been reported. We evaluated adherence to these recommendations by physicians at infusion centers and then piloted a program of supervision of monitoring by pharmacists. Methods: Phase I: We performed a retrospective case–control study of patients who received OPAT over 1 year at 2 hospital infusion centers. Controls were patients treated by an infectious diseases (ID) physician, and cases were those without an ID physician. Patients were excluded if they received fewer than 3 days of OPAT. Clinical pharmacy monitoring services were then implemented for patients on OPAT prescribed by non-ID physicians at 1 hospital's infusion unit. Two outcomes were measured: adherence to guidelines on monitoring and attainment of goal vancomycin and aminoglycoside serum concentrations when appropriate. The results for non-ID physicians were compared to both ID physicians and subsequently a pharmacist. Results: Ninety-nine patients were included in the retrospective study. Compared with patients who had ID physician supervision, the non-ID physicians who prescribed OPAT for 39 patients had lower adherence to monitoring recommendations (35.9% vs 68.3%, P = .003). No difference could be detected in achievement of goal vancomycin and aminoglycoside serum concentrations for the 14 cases and 19 controls requiring therapeutic drug monitoring (57.1% vs 68.4%, respectively, P = .765). Seven patients were enrolled in the study after pharmacy monitoring was implemented. Adherence to monitoring recommendations for these patients was significantly improved compared to the prior patients who lacked ID physician supervision (35.9% vs 100%, P = .0065). Conclusion: Non-ID physicians are less likely to monitor OPAT according to the IDSA guidelines than ID physicians; however, pharmacist oversight improves adherence to recommendations. Further studies of monitoring of OPAT by pharmacists should investigate the impact of pharmacist involvement on prevention of adverse events and hospital readmissions.